Characterization of the Primary Metabolome of Brachystegia boehmii and Colophospermum mopane under Different Fire Regimes in Miombo and Mopane African Woodlands - Duvane, Jossias A.; Jorge, Tiago F.; Maquia, Ivete; Ribeiro, Natasha; Ribeiro-Barros, Ana I. F.; António, Carla (Frontiers in Plant Science, 2017)
Miombo and Mopane are ecological and economic important woodlands from Africa, highly affected by a combination of climate change factors, and anthropogenic fires. Although most species of these ecosystems are fire tolerant, the mechanisms that lead to adaptive responses (metabolic reconfiguration) are unknown. In this context, the aim of this study was to characterize the primary metabolite composition of typical legume trees from these ecosystems, namely, Brachystegia boehmii (Miombo) and Colophospermum mopane (Mopane) subjected to different fire regimes. Fresh leaves from each species were collected in management units and landscapes across varied fire frequencies in the Niassa National Reserve (NNR) and Limpopo National Park (LNP) in Mozambique. Primary metabolites were extracted and analyzed with a well-established gas chromatography time-of-flight mass spectrometry metabolomics platform (GC-TOF-MS). In B. boehmii, 39 primary metabolites were identified from which seven amino acids, two organic acids and two sugars increased significantly, whereas in C. mopane, 41 primary metabolites were identified from which eight amino acids, one sugar and two organic acids significantly increased with increasing fire frequency. The observed changes in the pool of metabolites of C. mopane might be related to high glycolytic and tricarboxylic acid (TCA) rate, which provided increased levels of amino acids and energy yield. In B. boehmii, the high levels of amino acids might be due to inhibition of protein biosynthesis. The osmoprotectant and reactive oxygen species (ROS) scavenging properties of accumulated metabolites in parallel with a high-energy yield might support plants survival under fire stress.